2013
DOI: 10.12688/f1000research.2-72.v1
|View full text |Cite
|
Sign up to set email alerts
|

A p53-like transcription factor similar to Ndt80 controls the response to nutrient stress in the filamentous fungus, Aspergillus nidulans

Abstract: The Aspergillus nidulans xprG gene encodes a putative transcriptional activator that is a member of the Ndt80 family in the p53-like superfamily of proteins. Previous studies have shown that XprG controls the production of extracellular proteases in response to starvation. We undertook transcriptional profiling to investigate whether XprG has a wider role as a global regulator of the carbon nutrient stress response. Our microarray data showed that the expression of a large number of genes, including genes invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 64 publications
(106 reference statements)
2
26
0
Order By: Relevance
“…The increased induction levels of the structural GlcNAc catabolic genes in T. reesei in response to GlcNAc (Fig. 3) are substantially higher (> 100-fold) than for any gene mentioned by Katz et al (2013) in their genome-wide transcriptome analysis of carbon starvation in A. nidulans. Nevertheless, one of the best induction ratios comparing xprG + and xprG − strains (6-fold) was reported for hxkC.…”
Section: N-acetylglucosamine Catabolism Inmentioning
confidence: 82%
See 1 more Smart Citation
“…The increased induction levels of the structural GlcNAc catabolic genes in T. reesei in response to GlcNAc (Fig. 3) are substantially higher (> 100-fold) than for any gene mentioned by Katz et al (2013) in their genome-wide transcriptome analysis of carbon starvation in A. nidulans. Nevertheless, one of the best induction ratios comparing xprG + and xprG − strains (6-fold) was reported for hxkC.…”
Section: N-acetylglucosamine Catabolism Inmentioning
confidence: 82%
“…While in S. cerevisiae Ndt80 is primarily involved in the regulation of meiosis, the Ndt80-like proteins in N. crassa (VIB-1, FSD-1) have other functions. Mutations in fsd-1 affected the timing and development of female reproductive structures and ascospore maturation (Hutchison and Glass, 2010), and the A. nidulans homolog, ndtA, is apparently required for sexual reproduction (Katz et al, 2013). Further, VIB-1 is involved in the regulation of vegetative incompatibility and programmed cell death.…”
Section: Organisation Of the Glcnac Catabolic Gene Cluster In Filamenmentioning
confidence: 99%
“…mcrA is a master transcription regulator mcrA regulates several SM BGCs and this implies that it is involved in the regulation of transcription of many genes involved in SM biosynthesis. Secondary metabolism is intimately connected to a number of other processes in the cell, however, such as primary metabolism and development Katz et al, 2013;de Souza et al, 2013;Brakhage, 2013;Garzia et al, 2013). We wished to determine, therefore, if the effects of mcrA on gene expression extended beyond genes involved in secondary metabolism.…”
Section: Upregulation Of An8694 Results In Downregulation Of Secondarmentioning
confidence: 99%
“…Further supporting this deduction are the two E. festucae E437 nonantifungal mutants we isolated recently, T547 and T692, which show extracellular protease activity comparable to that of wild-type E437 (T. Hashikawa and D. Takemoto, unpublished data). Altogether, the data show that, given that NDT80/PhoG- type transcription factors of S. cerevisiae, C. albicans, and A. nidulans have large numbers of direct target genes (45,49,51), it is likely that the genes for the production of inhibitory metabolites in E. festucae, rather than the cell lytic enzymes, are critical targets of VibA for the antifungal activity of the endophyte.…”
Section: Discussionmentioning
confidence: 88%
“…Deletion mutants of xprG cannot utilize proteins as a carbon or nitrogen source (50). More recently, Katz et al (51) reported that XprG regulates a large number of genes in response to carbon starvation, including the genes required for the production of secondary metabolites, such as penicillin and sterigmatocystin. The E. festucae vibA mutant, like the N. crassa vib-1 and A. nidulans xprG mutants (39,50), is also defective in the production of extracellular protease.…”
Section: Discussionmentioning
confidence: 99%